CODE MIXING IN “BROWN SUGAR BATTLE” YOUTUBE VIDEO BY TITAN TYRA - Virginia, Fanny; Ambalegin, Ambalegin (IdeBahasa, 2021)
This descriptive qualitative research essentially aimed to find out the types of code mixing on Brown Sugar Battle video. Titan Tyra published the video on June 17th, 2019. The researchers chose the utterances of Titan Tyra that contained code mixing as the data source of this research. In collecting the data, the researchers conducted observational method and non-participatory technique. Additionally, in analyzing the data, the researchers applied bilingual-differentiating identification method and differentiating comparative link technique. Furthermore, the researcher applied the theory of code mixing proposed by Muysken (2000). The result revealed that the speaker frequently inserted English words and phrases in the utterance of Indonesian language. The speaker mixed language to do the review of brown sugar drink. From 53 data, there were 31 data of insertion and 22 data of congruent lexicalization. The type of insertion became the most frequently uttered type. Also, the speaker did not utter English clause in utterances.